Is the choice of conservation measures influenced by the targeted natural habitats? The case of French coastal Natura 2000 sites. (15th June 2017) - Duhalde, Michel; Levrel, Harold; Guyader, Olivier
Abstract: Natura 2000 (N2K) is a European network of protected areas that has grown out of the implementation of the Birds Directive (1979) and the Habitats Directive (1992). To date, the literature focussing on "conservation measures" required by the directives has been scarce. This article contributes to a better understanding of associated practices with regard to these measures in the case of France. We put forward a quantitative approach based on 1378 "action-sheets" randomly extracted from 113 management documents of French Natura 2000 coastal sites. These action-sheets are considered to be the physical embodiment of the notion of the conservation measure itself. The analysis concentrates on the "type" of the proposed measures, expressed in terms of a 9-category public policy instrument typology. In terms of frequency of quotation, we show the specific expected importance of three instruments: the work of Natura 2000 project managers, ecological/civil engineering, and data production. Awareness-raising is the main expected means to the end of countering harmful practices and detrimental behaviours. We then propose an exploratory analysis of contextual variables explaining the choice of the type of measure, with an AIC-based procedure of model selection and averaging. The interest of this approach is exemplified by a focus on five explanatory variables reflecting the kind of natural habitats concerned by the measures. Our results show the specificity of instruments associated with coastal habitats. In particular, whereas coastal terrestrial habitats are statistically managed by physical measures (physical regulation and engineering), methods for managing coastal marine habitats are geared towards, on the one hand, awareness raising and participatory approaches, and on the other, regulatory approaches and an integration of Natura 2000 objectives into exogenous institutional frameworks. The results we obtained shed light on the limits and prospects of the implementation of the Natura 2000 program in the marine environment. Highlights: Conservation measures for French Natura 2000 coastal sites are studied. A quantitative analysis of the factors explaining these measures is carried out. Coastal and marine habitats exhibit clear specificities of management orientations. The marine sites may be more dependent on exogenous institutional frameworks.